Entre trabalho remoto e presencial: um estudo sobre a temporalidade de professoras do ensino superior - Paiva, Marinara Nobre (2023)
The present study aims to analyze the temporality of higher education teachers' experience in remote work and face-to-face work. It is assumed that the covid-19 pandemic increased the overload of productive and reproductive work, as well as intensified the stress of teachers due to the remote work modality. In this way, when considering time as the main category of the study, it is believed that time is gendered, that is, it is managed differently for men and women due to the sexual division of labor. The research was developed based on the principles of Lev's Historical-Cultural Psychology method. S. Vygotsky. Eight professors from a Higher Education Institution (HEI) in the State of Ceará participated in the study. As a data collection instrument, the participants were asked to build a calendar through a semi-structured interview. Data were analyzed based on Gonzalez-Rey's constructive-interpretative analysis. Thus, it was noticed that most higher education teachers were overwhelmed by productive work in a pandemic context. This occurred due to the inadequacy of work activities in the domestic sphere and the intensification and precariousness of work. The reproductive activities of caring for the children and the house also occupied part of the teachers' temporality. Their work routines went beyond the formal workload due to the confluence of productive and reproductive work throughout the day. In this sense, being in social isolation gave a false feeling of having more time. Upon returning to face-to-face activities, a double demand for work was noted for activities started in the remote period that had to be continued in this resumption. Technological tools left traces of work intensification and surpassed the dimensions of working and non-working time in the teachers' reality. The teachers' working time was made possible by outsourcing domestic activities to other women for pay, which also had repercussions on free time and self-care. It is concluded that the temporality of most participants was measured by the sexual division of work, precariousness and work overload in ERE times, which reduced the possibilities of enjoying free/leisure time. When resuming face-to-face activities, it was possible, by delegating paid reproductive work and by the age of the children. The experiences were different according to the race, class, age of the children and sexual orientation of the participants.